Developing "I Am Smart" Media for Increasing Learning Motivation of Students with Autism Spectrum Disorders - Salsyabila, Gita; Habiby, Wahdan Najib (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The aim of this research was to develop "I Am Smart" media and evaluate its effectiveness in increasing the learning motivation of students with autism spectrum disorders. In order to accomplish this objective, this form of investigation was created. Consequently, the R&D model was utilized in this investigation. Potential problems, data collection, product design, design validation, product design revision, and trial use were the phases of the development model. Twenty autistic third-graders from SD Muhammadiyah 01 Tanjung Enim made up the sample for this investigation. This study's sample consisted of one pupil. The sampling method utilized was non-probability sampling. Observation, assessments, interviews, and questionnaires were employed as methods for data collection. This development research employs descriptive analysis, learning content analysis, and analysis of test results for its analysis. This study's primary data came from questionnaires, assessments, and interviews with field informants, so they conveyed pertinent information. These data were collected from students and their teachers. In this study, the secondary data were books, journals, and mass media about learning media. The average score for the "I Am Smart" media validation assessment by media experts was 90% (very valid), while the average score for the validation assessment by material experts was 80% (valid), and the average score for the validation assessment by field test experts was 87% (very valid). Based on these results, it can be concluded that the "I Am Smart" learning media is valid for use with students with autism. Before receiving "I Am Smart" learning media on the first to third trials, the subject received a score of 30; however, after receiving "I Am Smart" learning media, the subject demonstrated that "I Am Smart" learning media could help the subject increase in value by achieving the highest score of 75. According to the results of the initial trial and the results of the final trial, "I Am Smart" learning media effectively encourages or motivates students with autism spectrum disorders to engage in learning activities, making it appropriate for students with autism spectrum disorders.